2013
DOI: 10.1016/j.psyneuen.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Basal regulation of HPA and dopamine systems is altered differentially in males and females by prenatal alcohol exposure and chronic variable stress

Abstract: Effects of prenatal alcohol exposure (PAE) on central nervous system function include an increased prevalence of mental health problems, including substance use disorders (SUD). The hypothalamic-pituitary-adrenal (HPA) and dopamine systems have overlapping neurocircuitries and are both implicated in SUD. PAE alters both HPA and dopaminergic activity and regulation, resulting in increased HPA tone and an overall reduction in tonic dopamine activity. However, effects of PAE on the interaction between HPA and dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 54 publications
4
52
2
Order By: Relevance
“…Although consistent with the literature, our current findings are notable owing to the relatively mild stressors incorporated into the CMS regimen, and provide a longitudinal approach to begin to elucidate the possible relationship between PAE, adolescent experience, and dysregulated HPA function on cognitive performance in adulthood. Of note, these relationships may not be unique to adolescent experiences, as we have shown previously that basal corticosterone levels are increased in control, but not PAE, females following CMS exposure in adulthood, suggesting that PAE may blunt the normal change in basal CORT levels during CMS in adulthood as well (Uban et al, 2013). Moreover, chronic stress may affect males and females differently.…”
Section: 1 Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although consistent with the literature, our current findings are notable owing to the relatively mild stressors incorporated into the CMS regimen, and provide a longitudinal approach to begin to elucidate the possible relationship between PAE, adolescent experience, and dysregulated HPA function on cognitive performance in adulthood. Of note, these relationships may not be unique to adolescent experiences, as we have shown previously that basal corticosterone levels are increased in control, but not PAE, females following CMS exposure in adulthood, suggesting that PAE may blunt the normal change in basal CORT levels during CMS in adulthood as well (Uban et al, 2013). Moreover, chronic stress may affect males and females differently.…”
Section: 1 Discussionmentioning
confidence: 60%
“…In some instances, females may be more sensitive to the effects of chronic stress in terms of hormonal stress response, showing greater changes in hormone secretion after being exposed to the same stressors as males (Galea et al, 1997, Cameron, 2004). Relevant to this point, in contrast to the differences in basal CORT levels observed in PAE compared to control females, Uban and colleagues (Uban et al, 2013) found no differences in basal CORT levels between PAE and control males following CMS, highlighting the importance of sex differences in the investigation of PAE-related responses to early and later life environmental stressors.…”
Section: 1 Discussionmentioning
confidence: 96%
“…Given the sexually dimorphic effects of PAE (Goodlett and Peterson, 1995; Uban et al, 2013; Weinberg et al., 2008), as well as the striking gender differences in microglia colonization during development (Schwarz et al, 2012), we included both males and females in this study. In the DG, we detected no difference in the LPS-induced pro-inflammatory response between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal ethanol exposure affects the interrelation of the dopaminergic system with the hypothalamic-pituitary-adrenal (HPA) axis. This effect is sex dependent (Uban et al, 2013). Specifically, males are characterized by low testosterone levels, which may reduce their capacity to control the HPA axis responsiveness to stimuli, something that is not reported among females (Uban et al, 2013).…”
Section: Pathophysiologic and Epigenetic Pathways That Contribute To mentioning
confidence: 99%